The Role of Ethical Leadership in Achieving Strategic Leadership - احمد اسماعيل, جبرائيل; پيرداود عزيز, كامران (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
General framework: The general framework represents the study problem, which was identified by raising several questions about the nature of the relationship, the impact, and the variance between independent variable ethical leadership, and dependent variable strategic entrepreneurship. All hypotheses were subjected to multiple tests, and the study used a questionnaire as a tool to colect data. Objective: The current study aimed to explore the role of ethical leadership in achieving strategic entrepreneurship, the dimensions of ethical leadership were the availability of ethical behavior, ethical behavior practices, and enhancing ethical behavior. While the dimensions of strategic entrepreneurship were risk Taking, creativity and innovation, entrepreneurial leadership, and proactiveness. Methodology: The study used descriptive analytical approach, as the main and sub-variables were described, as well as analyzing the relationships and influence between the variables. The survey participants were reached (117) members of the college deans, vice deans, and heads of departments and they represent the study sample. The hypotheses were tested by using SPSS V.22 program. Main Results: The study reached several conclusions, the presence of a positive and significant relationship between ethical leadership and strategic entrepreneurship at the macro and micro level; this confirmed the benefit of the surveyed colleges from ethical leadership and its contribution to achieving strategic entrepreneurship and overcoming competitors. In addition, the results showed a positive and significant effect of ethical leadership in strategic entrepreneurship. Main Recommendations: The researcher recommended that academic leaders in the faculties of Salahaddin University must adopt ethical leadership practices and not neglect them whenever possible to achieve strategic entrepreneurship by academic members. The study also has some suggestions regarding future studies.